A Mobile App, KhunLook, to Support Thai Parents and Caregivers With Child Health Supervision: Development, Validation, and Acceptability Study - Areemit, Rosawan; Lumbiganon, Pagakrong; Suphakunpinyo, Chanyut; Jetsrisuparb, Arunee; Sutra, Sumitr; Sripanidkulchai, Kunwadee (JMIR Publications, 2020)
BackgroundIn Thailand, children born in government hospitals receive a maternal and child health handbook (MCHH). However, when a new MCHH edition is released, those with the previous editions do not have access to the updated information. A mobile app is an appealing platform to fill this gap. We developed a mobile app called "KhunLook" as an interactive electronic MCHH intended to assist parents in child health supervision. ObjectiveThis study describes the user requirements and development of the KhunLook mobile app, validity of parents' growth assessments, and parents' evaluation of feasibility and acceptability of the app. MethodsPhase 1 was a qualitative study using individual interviews. The interview data were used to revise the prototype. In phase 2, parents were randomly assigned to assess their children's growth with the app or the MCHH. The outcomes were compared to those of the physician's assessment, and congruence was determined. In phase 3, parents evaluated the feasibility and acceptability of the app in comparison to the MCHH through a web-based survey. ResultsFour health care providers and 8 parents participated in phase 1. Two themes were identified: (1) the mobile app potentially counters parents' infrequent use of the MCHH with accuracy, attractiveness, convenience, and simplicity, and (2) health supervision needs to be standard, up-to-date, and understandable. KhunLook was publicly launched with a family page and 7 key features: growth and nutrition, development, immunizations, oral health, reminders for the next appointment, memories, and health advice. In phase 2, 56 parents participated in the growth parameter assessments; 34 were in the App group and 22 in the MCHH group. The outcomes of the growth parameter assessments between parents and physicians in both the App and MCHH groups were not significantly different. The congruence proportions were higher in the App group for weight and head circumference, but the differences were not statistically significant. In phase 3, 356 parents from all over Thailand participated in a web-based survey. Parents rated the app feasibility as "very easy to easy" to use at higher proportions than the MCHH in all health assessment domains (growth, development, and immunizations) and ease-of-use domains with statistical significance (P<.001). The KhunLook app received a significantly higher mean score (8.59/10) than the MCHH (7.6/10) (P<.001). Most parents (317/356, 89.0%) preferred the app over MCHH. Further, 93.5% (333/356) of the parents stated that they would continue to use the app and 96.9% (345/356) would recommend others to use it. ConclusionsKhunLook, a Thai mobile app for child health supervision, was developed, validated for growth assessments, and was well accepted for ease-of-use by parents. Further studies should be conducted with a large scale of users, and the impact of this app on health behaviors and health outcomes must be evaluated.